The 'Hawk-Dove' game and the speed of the evolutionary process in small heterogeneous populations - Bernhard Voelkl (Games, 2010)
I study the speed of the evolutionary process on small heterogeneous graphs using the Hawk-Dove game. The graphs are based on empirical observation data of grooming interactions in 81 primate groups. Analytic results for the star graph have revealed that irregular graphs can slow down the evolutionary process by increasing the mean time to absorption. Here I show that the same effects can be found for graphs representing natural animal populations which are much less heterogeneous than star graphs. Degree variance has proven to be a good predictor for the mean time to absorption also for these graphs.
Keywords: 330; evolutionary game theory; heterogeneity; games on graphs